The impact of work-family factors in the relationships between organizational and occupational characteristics and intention to stay - Noraani Mustapha (2012)
In this study work-family factors were examined as mediating variables on the relationships between organizational and occupational characteristics as the independent variables and intention to stay as the dependent variable. Self-administered research questionnaire was utilized for data collection and data was collected from 240 middle age single mother employees in Klang Valley, Malaysia. Samples were determined through simple random sampling method from six single mother associations. Descriptive statistical analysis was conducted to describe the respondents. Pearson Product Moment Correlation was used to determine the relationships among variables and Structural Equation Modeling using AMOS version 16.0 was utilized for model testing and to verify the presence of mediation effects. Further, the Soble’s z-test was used to test whether the mediators carry the effect of the independent variables on the dependent variable. The findings indicated that there were positive and negative relationships among variables. The results also established the presence of mediation effects between the independent and dependent variables. Organizations may utilize work-family factors as mechanism to promote longer retention among employees.